EVALUASI PENGENDALIAN BIAYA DAN WAKTU PADA PROYEK PEMBANGUNAN JALAN STRATEGIS MATANG SIJUEK-TRIENG PANTANG DENGAN MENGGUNAKAN METODE EARNED VALUE - Alfian Alfian (Politeknik Negeri Lhokseumawe, 2016)
Time and cost are important aspects in a construcrtion project to achieve a desired success of the project. One way to control cost and time is to use earned value analysis (return value) that informs the data against the cost and time accurately and clearly. The purpose is to evaluate the amount of cost and usage time has been used in the on road paving projects in the Idi city sub district idi rayeuk district east aceh. The method used in this study is the concept of the value of the result (earned value analysis) examines the tendency of schedule variance and cost variance at a period during the project. By conducting this study of earned value project completion with BCWP =Rp.253,429,607.35 BCWS = Rp. 897,091, 753.ll and ACWP = Rp. 306,453,335. 79. Judging from the cost variance (CV) 0, with cost performance index (CPI) l in order to get project completion cost of Rp6,564,l 33,232. While aspects of the project Schedule is extra time -29.2% or 31 weeks ahead ofplan indicated SPI value 1.Keywords : Cost, Performance, earned value, varians, index.